Functional and Nutritional Characteristics of Wheat Grown in Organic and Conventional Cropping Systems. Issue 5 (6th April 2015) - Park, Eun Young; Baik, Byung‐Kee; Miller, Perry R.; Burke, Ian C.; Wegner, Eric A.; Tautges, Nicole E.; Morris, Craig F.; Fuerst, E. Patrick
Abstract : The effects of organic versus conventional farming practices on wheat functional and nutritional characteristics were compared. Soft white winter wheat and hard red spring wheat were obtained from multiyear replicated field plots near Pullman, Washington, and Bozeman, Montana. Test weight, kernel weight, and kernel diameter tended to be greater in both soft and hard organic wheat than in conventional wheat in the Pullman studies. Phenolic content and total antioxidant capacity tended to be lower in organic than in conventional wheat. Flour ash, P, and Mg contents in whole wheat flour varied in parallel among cropping systems, but levels were not consistently associated with either organic or conventional cropping systems. Protein contents of whole wheat and refined flours were similar in organic and conventional wheat from Pullman when fertility levels were similar. Higher fertility was associated with higher protein content in both organic and conventional cropping systems. Soft wheat flour from a low‐fertility organic cropping system had lower sodium carbonate, lactic acid, and sucrose solvent retention capacities, lower protein content, and greater cookie diameter and cake volume than soft wheat flour from the higher fertility organic and conventional cropping systems; the change in end‐product quality was significant in one out of two crop years. In the Bozeman hard wheat studies, higher fertility in both organic and conventional cropping systems tended to increase protein content and bread loaf volume. Results indicated that neither organic nor conventional cropping systems were associated with substantially improved mineral and antioxidant nutritional properties, and end‐use quality of wheat was more strongly associated with fertility level than with organic versus conventional cropping systems.